Antigen Conjugated to Anti‐CD23 Antibodies is Rapidly Transported to Splenic Follicles by Recirculating B Cells. (January 2015) - Xu, H.; van Mechelen, L.; Henningsson, F.; Heyman, B.
Abstract IgE–antigen complexes, administered intravenously to mice, induce a several 100‐fold higher specific antibody response than antigen alone. Additionally, in vivo activation and proliferation of specific CD4+ T cells is enhanced. The mechanism behind these effects is thought to be that peripheral B cells capture IgE–antigen complexes via their low‐affinity receptor for IgE, CD23, and rapidly transport them to splenic B cell follicles where an immune response is initiated. Here, we demonstrate that ovalbumin, covalently coupled to anti‐CD23 antibodies and administered intravenously to mice, is also transported to splenic follicles and induces an enhanced primary antibody response. These effects are absent in CD23‐deficient mice. No enhanced induction of immunological memory was observed. These findings extend previous observations regarding the in vivo role of CD23 and emphasize that recirculating B cells play an important role in antigen transport to the spleen.